Chemico-pharmacological evaluations of the dwarf elephant ear (Colocasia affinis Schott) plant metabolites and extracts: health benefits from vegetable source - Safaet Alam; Safaet Alam; Fahmida Tasnim Richi; Hasin Hasnat; Firoj Ahmed; Nazim Uddin Emon; Md. Jasim Uddin; G. M. Masud Rana; Shuanghu Wang; Mst. Sarmina Yeasmin; Nazim Uddin Ahmed; Md. Salim Khan; et al. (Frontiers Media S.A., 2024)
Introduction:Colocasia affinis Schott (Family: Araceae), found in the Asian region, is a traditional root vegetable consumed by the locals and well-known as Dwarf Elephant Ear.Methods: For the pharmacological exploration of this root vegetable, four kupchan fractions (i.e. HSF, DCMSF, EASF, and AQSF) from ethanolic extract of C. affinis were employed to in vitro i.e. antioxidant, cytotoxicity, and antimicrobial and in vivo i.e. antidiarrheal and analgesic assays, followed by phytochemical screening and GC-MS protocol.Result and Discussion: In the antioxidant assay, the AQSF showed promising potential with an IC50 value of 29.4 μg/mL and additionally, it exhibited the greatest overall phenolic content, measuring 57.23 mg GAE/gm. of extract among other fractions. The AQSF also revealed promising cytotoxic activity in brine shrimp lethality assay with an LC50 value of 1.36 μg/mL. Both AQSF and EASF exhibited substantial antimicrobial efficacy against both gram-positive and gram-negative bacteria as well as various fungus species with a remarkable zone of inhibitions compared to standards. Whereas, during both the castor oil-induced antidiarrheal and acetic acid-induced writhing assay, the DCMSF at 400 mg/kg dose exhibited the highest 51.16% reduction of diarrhea and 52.33% reduction of writhing. Phytochemical screening revealed several chemical groups while GC-MS study of different fractions of dwarf elephant ear ethanolic extract revealed 48 different bioactive phytochemicals in total. Several targets such as KAS, DHFR for anti-microbial activities, GLR, URO for antioxidant activities, EGFR, BCL-2 for cytotoxicity, KOR, DOR for antidiarrheal activities and COX-2, TNF-α for analgesic activities are considered for molecular docking against identified phytocompounds and standards along with ADME/T studies to ascertain their safety, efficacy and drug likeliness profiles.Conclusion: To recapitulate, our study revealed that vegetables such as dwarf elephant ear can be considered as a prospective source of therapeutics and drug development besides their nutritive food values.